Advances in Immunosuppressive Agents Based on Signal Pathway - Xu, Zhiqing; Chu, Ming (Frontiers in Pharmacology, 2022)
Immune abnormality involves in various diseases, such as infection, allergic diseases, autoimmune diseases, as well as transplantation. Several signal pathways have been demonstrated to play a central role in the immune response, including JAK/STAT, NF-κB, PI3K/AKT-mTOR, MAPK, and Keap1/Nrf2/ARE pathway, in which multiple targets have been used to develop immunosuppressive agents. In recent years, varieties of immunosuppressive agents have been approved for clinical use, such as the JAK inhibitor tofacitinib and the mTOR inhibitor everolimus, which have shown good therapeutic effects. Additionally, many immunosuppressive agents are still in clinical trials or preclinical studies. In this review, we classified the immunosuppressive agents according to the immunopharmacological mechanisms, and summarized the phase of immunosuppressive agents.